2021
DOI: 10.21744/lingcure.v5ns1.1605
|View full text |Cite
|
Sign up to set email alerts
|

organization's climate againts the work motivation

Abstract: The organizational climate is a collection of attitudes and beliefs related to the organization that is perceived and collectively implemented by members of the Organization as a whole. This research aims to know the organization's climate for employees' work motivation at the Regional Civil Service Agency and the statistics of Bone District. This study uses the type of exploitive research with a quantitative approach (positivism). This research uses two types of data, namely secondary and primary data. The da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…This research supports the research conducted by Kumar (2021) that organizational climate has a significant influence on employee motivation. Zainal et al (2021) also found that the organizational climate is positively and significantly related to employee work motivation. Organizational climate can be applied through rules and policies to feel responsible in carrying out tasks and responsibilities.…”
Section: E the Effect Of Organizational Climate On Work Motivationmentioning
confidence: 84%
See 1 more Smart Citation
“…This research supports the research conducted by Kumar (2021) that organizational climate has a significant influence on employee motivation. Zainal et al (2021) also found that the organizational climate is positively and significantly related to employee work motivation. Organizational climate can be applied through rules and policies to feel responsible in carrying out tasks and responsibilities.…”
Section: E the Effect Of Organizational Climate On Work Motivationmentioning
confidence: 84%
“…Chumba et al (2018) found that extrinsic rewards (77.3%) were considered to be a stronger predictor of nurse performance at Kenya National Referral Hospital compared to intrinsic rewards (64.9%). Zainal et al (2021) state that the organizational climate has a positive and significant relationship to employee work motivation.…”
Section: E Previous Studymentioning
confidence: 99%